2011
DOI: 10.1002/pssc.201100215
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pd‐Au/MWCNTs surface treatment on catalytic activity in the formic acid electrooxidation

Abstract: Influence of different treatments of Pd‐Au/MWCNTs prepared by a modified polyol microwave‐assisted method on the morphology and the catalytic activity in the formic acid electrooxidation was investigated. The following standard treatments were applied to purify the metal particles surface from the carbonaceous deposits formed from ethyl glycol adsorbed on the catalyst after the preparation: 1. annealing in air at 300 °C, 2. annealing in air at 300 °C and then reduction in 5%H2/Ar at 200 °C, 3. reduction in 5%H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Recently, various palladium-based bimetallic nanostructures (such as palladium-copper, palladium-platinum, and palladium-gold) with well-defined morphologies, excellent catalytic activities, and stabilities have been widely reported [4][5][6][7][8]. Among them, palladium-gold (Pd-Au) bimetallic nanocrystals, especially gold@palladium (Au@Pd) core-shell nanostructures have been widely used as effective catalysts for methanol oxidation reaction [9][10][11], oxygen reduction reaction [12,13], formic acid oxidation reaction [14], and ethanol oxidation reaction (EOR) [15][16][17][18], etc. For example, Lu and co-workers demonstrated that Au@Pd core-shell nanocrystals with octahedral shape exhibited the electrocatalytic activity increased by 2 times than these nanocrystals with other shapes for the EOR [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various palladium-based bimetallic nanostructures (such as palladium-copper, palladium-platinum, and palladium-gold) with well-defined morphologies, excellent catalytic activities, and stabilities have been widely reported [4][5][6][7][8]. Among them, palladium-gold (Pd-Au) bimetallic nanocrystals, especially gold@palladium (Au@Pd) core-shell nanostructures have been widely used as effective catalysts for methanol oxidation reaction [9][10][11], oxygen reduction reaction [12,13], formic acid oxidation reaction [14], and ethanol oxidation reaction (EOR) [15][16][17][18], etc. For example, Lu and co-workers demonstrated that Au@Pd core-shell nanocrystals with octahedral shape exhibited the electrocatalytic activity increased by 2 times than these nanocrystals with other shapes for the EOR [19].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing electrocatalytic activity of nanocomposite AuPd/VC‐5 with other reported carbon‐supported AuPd alloy nanocomposites is complicated by differences in metal alloy composition, nanocomposite physical properties, testing conditions, and electrochemical test method. AuPd(35:65)/multi‐walled carbon nanotube (MWCNT) nanocomposites prepared by polyol reduction of PdCl 2 and HAuCl 4 · 3H 2 O perform well as electrooxidation catalyst in formic acid/oxygen fuel cells giving maximum power density of 64 mW mg −1 AuPd at a current density of 135 mA mg −1 AuPd catalyst . Similarly prepared AuPd/MWCNT nanocomposites subjected to a post‐synthesis H 2 thermal reduction treatment give oxidation currents near 800 mA mg −1 total metal when tested on a rotating disk electrode in 3 M HCOOH/1 M H 2 SO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Among these, metal‐ and/or metal oxide‐decorated CNTs devoted a high interest because of their technological application in catalysis, bio/chemical sensoring, energy storage and production, individual electrical CNT properties studies, etc. For a catalytic purpose, the metal (mainly Pd substituting Pt) and AuPd catalysts supported multiwalled carbon nanotubes (MWCNTs), and recently, Pd‐ZrO 2 and AuPd‐ZrO 2 on functionalised MWCNTs (f‐MWCNTs) were applied. These Pd‐ and AuPd‐decorated f‐MWCNTs catalysts of formic acid (FA) electro‐oxidation (on an anode side), prepared with the same metal loading (20 wt%) using different methods, provided information on their higher catalytic activity exceeding the respective for Pt catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…For a catalytic purpose, the metal (mainly Pd substituting Pt) and AuPd catalysts supported multiwalled carbon nanotubes (MWCNTs), and recently, Pd‐ZrO 2 and AuPd‐ZrO 2 on functionalised MWCNTs (f‐MWCNTs) were applied. These Pd‐ and AuPd‐decorated f‐MWCNTs catalysts of formic acid (FA) electro‐oxidation (on an anode side), prepared with the same metal loading (20 wt%) using different methods, provided information on their higher catalytic activity exceeding the respective for Pt catalysts. The modified 20 wt% Pd‐ZrO 2 /f‐MWCNTs and 10 wt% Au 10 wt% Pd‐ZrO 2 /f‐MWCNTs catalysts showed smaller catalytic activity than the same catalysts without ZrO 2 because of larger nanoparticle size, however, were shown to be more resistant for deactivation and sintering of nanoparticles because of thermochemical treatment in oxygen and hydrogen.…”
Section: Introductionmentioning
confidence: 99%